2015
DOI: 10.1002/2014wr016068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tidal fluctuations and spatial heterogeneity on mixing and spreading in spatially heterogeneous coastal aquifers

Abstract: We study the combined effect of heterogeneity in the hydraulic conductivity field and tidal oscillations on the three-dimensional dynamics of seawater intrusion in coastal aquifers. We focus on the quantification of its impact on solute mixing and spreading of the freshwater-seawater interface. Threedimensional Monte Carlo realizations of log-normally distributed permeability fields were performed, and for each realization, numerical variable density flow and solute transport simulations were conducted. Mixing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 57 publications
5
60
0
Order By: Relevance
“…However, a mitigating feature found in many catchments is consistent with findings elsewhere (Pool et al, 2015). The degree of mixing by tidal circulation may be variable 10 in space along the beachface, as suggested by the differences in chloride concentrations at the base of the porewater profiles.…”
Section: Discussionsupporting
confidence: 86%
“…However, a mitigating feature found in many catchments is consistent with findings elsewhere (Pool et al, 2015). The degree of mixing by tidal circulation may be variable 10 in space along the beachface, as suggested by the differences in chloride concentrations at the base of the porewater profiles.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings are consistent with previous studies (e.g. Pool et al, 2015) in showing that an analysis relying on the ensemble concentration field tends to overestimate significantly the degree of mixing and spreading of the solute.…”
supporting
confidence: 93%
“…These outcomes (hereafter called rotation effects) are consistent with previous literature findings. In particular, Kerrou and Renard (2010) and Pool et al (2015) observed that the strength of the rotation effect increases with the variance of the log-15 permeability field. Abarca (2006Abarca ( , 2007 showed that a similar effect can be observed in a homogenous domain when considering increasing values of the dispersion coefficient.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kuan et al [2012] illustrated through numerical modelling combined with laboratory experiments that in tidally-influenced aquifers where an USP forms, the extent of seawater intrusion into the aquifer is significantly reduced compared to non-tidal conditions. More recently, Pool et al [2014] and Pool et al [2015] conducted numerical analyses to quantify the effect of tides on the saltwater wedge DZ in homogeneous and heterogeneous CUAs. They showed the extent of mixing is influenced by the tidal amplitude, tidal period and hydraulic diffusivity, with the aquifer heterogeneity reducing the impact of tides on the extent of mixing along the DZ.…”
Section: Tidesmentioning
confidence: 99%